2016
DOI: 10.1016/j.stem.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Inflammation Drives Genotoxic Stress in Hematopoietic Stem Cells and Predicts Disease Evolution in Human Pre-leukemia

Abstract: Mesenchymal niche cells may drive tissue failure and malignant transformation in the hematopoietic system, but the underlying molecular mechanisms and relevance to human disease remain poorly defined. Here, we show that perturbation of mesenchymal cells in a mouse model of the pre-leukemic disorder Shwachman-Diamond syndrome (SDS) induces mitochondrial dysfunction, oxidative stress, and activation of DNA damage responses in hematopoietic stem and progenitor cells. Massive parallel RNA sequencing of highly puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
308
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(319 citation statements)
references
References 67 publications
11
308
0
Order By: Relevance
“…26,73 For instance, in mice, damage-associated molecular pattern (DAMP) molecules S100A8/A9 DAMPs, are shown to activate TLR4 signaling in HSPCs and induce genotoxic stress, a mechanism by which niche cells may cooperate with aberrant HSPCs toward leukemogenic transformation. Notably, S100A8/A9 signaling in mesenchymal niche cells appears to be an independent predictor of disease outcome in human MDS.…”
Section: -94mentioning
confidence: 99%
See 1 more Smart Citation
“…26,73 For instance, in mice, damage-associated molecular pattern (DAMP) molecules S100A8/A9 DAMPs, are shown to activate TLR4 signaling in HSPCs and induce genotoxic stress, a mechanism by which niche cells may cooperate with aberrant HSPCs toward leukemogenic transformation. Notably, S100A8/A9 signaling in mesenchymal niche cells appears to be an independent predictor of disease outcome in human MDS.…”
Section: -94mentioning
confidence: 99%
“…Notably, S100A8/A9 signaling in mesenchymal niche cells appears to be an independent predictor of disease outcome in human MDS. 73 Moreover, S100A9 binding to CD33 is also reported to expand myeloid-derived suppressor cells, which contribute to the development of myelodysplastic phenotypes in mice. 97 Importantly, human myeloid-derived suppressor cells also express CD33 97 and their number correlates with the number of regulatory T cells and disease progression in MDS patients.…”
Section: -94mentioning
confidence: 99%
“…Next, Zambetti and colleagues analyzed the HSPCs and found that while their numbers were unaffected the transcriptional profile was similar to profiles associated with leukemic evolution of human CD34+ cells, specifically pathways linked to mitochondrial abnormalities were triggered (8). Further analysis of mitochondria found increased membrane potential leading to increased levels of reactive oxygen species (ROS); which activated DNA damage response and repair pathways indicated by accumulation of Ser139-phosphorylated H2AX histone (γH2AX) (8). Depletion of S-phase cells indicated cell cycle arrest at G1-S.…”
mentioning
confidence: 99%
“…Recently, Zambetti and colleagues identified the mechanism by which deletion of Sbds in this SDS mouse model causes disease. They found that increased inflammatory signals in the microenvironment caused genotoxic stress in both the mouse model and SDS patient samples (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation